Data Analysis of Ceramic Material Color Matching Collection Points in Furniture Design Based on the Image Difference Prediction Model. (28th March 2023) - Zhou, Cheng; Li, Yalan
Abstract : The manufacturing process of ceramic materials and exquisite patterns is not simply artistic acts. At the same time, it condensed the excellent traditional culture of ancient China. The application of ceramic materials in modern furniture can not only enhance the taste of living room culture but also show the charm of China's ceramic culture. Objective . To optimize the scientific data model required by traditional ceramic materials. On the basis of image difference prediction calculation, the data of ceramic material color matching collection points were analyzed and processed, and the image difference prediction model was established. This paper introduces the application and development of ceramic materials in furniture industry. On the basis of the traditional image difference prediction algorithm, the consideration of image difference and difference prediction expansion is added, and the image difference prediction calculation model of ceramic material color matching is established. The survey results show that 83% of customers are very satisfied with the color matching of new ceramic materials calculated by image difference prediction. This experiment uses image difference prediction model to remove the redundant pixels of ceramic material color and make multiple judgments on color display. According to the initial color data of the collection points, this experiment finally obtained a new combination color matching of ceramic wardrobe, which is more suitable for the "minimalist" and "quiet" styles.